Langkah Unggul Ke Arah Digital: Studi Kasus Kantin Kalibata Sebagai Pelatihan UMKM di Era Digital - Wahdi Fauzan Nugroho; Lingga Yuliana; Rendi Alfian; Didin Hikmah Perkasa (Jurnal Pelayanan Masyarakat, 2024)
The primary objective of training is allowing MSMEs to gain advantages from technology through providing businesses access to QR code viewers for electronic payment transactions. Personal guidance is provided in the Kalibata Canteen. The training program has been set for April 21, 2024, Sunday. MSMEs whose have not yet utilized digital payment media are the target audience for this training program. a review of what was discovered and the discussion before it, MSMEs who view technology as an instrument of expediting transactions need this training. MSMEs ought to comprehend the significance that digitization is to prospering in a disruptive society and ensuring business sustainability in the face of increased rivalry. Offering a supplementary payment option, such as scanning QRIS, is one way MSMEs utilize technology. Through implementation of technology, MSMEs may lead the way. In order encouraging MSMEs to be more widely accepted and for consumers to prefer shopping at MSMEs, both of these factors are improving.